Strategi Integrasi Usaha Hulu dan Hilirisasi Perikanan dengan Pendampingan dan Teaching Technology pada UMKM Potensial di Kota Palembang - Prariska, Donny; Adli; Syukerti, Nanda; Lestari, Siti; Sumsanto, Muhammad (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The waters in the Palembang region of South Sumatra have enormous potential to be exploited. Various aspects related to water potential, such as economic and food, social and cultural, and tourism, have shown a positive increasing trend if managed well. One of the potential MSMEs focused on water potential, especially fisheries, is IRT Palemas-preneur. The aim of this activity is to improve partners' capabilities by optimizing regional potential, implementing product diversification, and developing markets, accompanied by appropriate and consistent assistance. Community service activities in this business unit consist of several methods, namely counseling, training, mentoring, and evaluation. The results of the activities that have been carried out are increased capabilities, reduced production costs, and increased sales to business partners.